KREATIVITAS GURU TERHADAP PRAKTIK KERJA INDUSTRI SISWA KELAS XI AKUNTANSI SMK PEMBANGUNAN RASAU JAYA - Esi, Esi; Aminuyati, Aminuyati; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this thesis is ?The Influence Of Teacher Creativity On Industrial Work Practices Of Class XI Students Majoring In Accounting In Rasau Jaya Development Vocational Schools. This research aims to find out how big the influence of creativity on industrial work practices students in the rasau jaya development as resource persons and 38 students of class XI majoring in accounting as respondents. The method used is descriptive method with the aim of teacher cretivity in the Rasu Jaya development. Data collection tools use direct communication techniques, indirect communication teachniques, document study techiques. While data processing uses descriptive analysis. These reults state that the influence of teacher creativity on industrial work practices of class XI students majoring in accounting in Rasau Jaya Development Vocational School is 17%. Keywords : Teacher?s Creativity, Industrial Work Practices